1994
DOI: 10.1159/000236743
|View full text |Cite
|
Sign up to set email alerts
|

Degranulation from Human Eosinophils Stimulated with C3a and C5a

Abstract: It is unclear what actually induces eosinophil degranulation in vivo. We examined eosinophil cationic protein (ECP) release from normal human eosinophils (Eos) in response to C3a and C5a. C3a and C5a induced remarkable ECP release when Eos were preincubated with cytochalasin B. ECP release induced by C3a or C5a was greater than that induced by PAF at a concentration of 10––7M. The ED50 for ECP release was 3 × 10––8M and 3 × 10––9M for C3a and C5a, respecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
40
0
2

Year Published

1996
1996
2013
2013

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(42 citation statements)
references
References 1 publication
0
40
0
2
Order By: Relevance
“…Previous studies have shown that C3a can readily degranulate eosinophils, basophils, and mast cells (11,12) while also activating and modulating cytokine release from monocytes/macrophages (13). However, despite high expression of C3aR on neutrophils and a clear Ca 2+ mobilization response in response to C3a (or other C3aR ligands) (9,14), a clear role for C3a has not yet been ascribed to neutrophils (15), which form the vast majority of the granulocytic population.…”
mentioning
confidence: 99%
“…Previous studies have shown that C3a can readily degranulate eosinophils, basophils, and mast cells (11,12) while also activating and modulating cytokine release from monocytes/macrophages (13). However, despite high expression of C3aR on neutrophils and a clear Ca 2+ mobilization response in response to C3a (or other C3aR ligands) (9,14), a clear role for C3a has not yet been ascribed to neutrophils (15), which form the vast majority of the granulocytic population.…”
mentioning
confidence: 99%
“…3 and 5). In addition, C3a and C5a can stimulate respiratory burst in macrophages (6,7), neutrophils (8,9), and eosinophils (10); stimulate the release of histamine from basophils (11,12) and mast cells (13,14); and regulate the synthesis of eosinophil cationic protein and adhesion to endothelial cells by eosinophils (15)(16)(17). C3a can also stimulate serotonin release from platelets (18) and modulate synthesis of IL-6 and TNF-␣ by B lymphocytes and monocytes (19,20).…”
mentioning
confidence: 99%
“…glucoronidase [11], histamine [44] and eosinophil cationic protein (ECP) [17], stimulation of granulocyte and monocyte oxidative burst with the release of reactive oxygen species [12,13,45,46], an increased expression of b 2 -integrin adhesion molecules and shedding of L-selectin [14], an increase in vascular permeability [2,3] and delayed neutrophil apoptosis [16]. These mechanisms of C5a have been implicated in the induction of a potent inflammatory response and the prolongation of the life span of neutrophils in the presence of foreign antigens [16].…”
Section: Normal Pregnancymentioning
confidence: 99%
“…Its interaction with phagocytic cells increases oxidative burst [12,13], induces expression of adhesion molecules [14,15] and inhibits polymorphonuclear (PMN) apoptosis [16]. C3a effects are predominantly on mast cells and eosinophils, and include chemotaxis [10,11], granule release [11,17], expression of adhesion molecules (b 2 integrin) and L-selectin shedding [14]. C4a, the weakest anaphylatoxin [4], can only be generated through the classical pathway.…”
Section: Introductionmentioning
confidence: 99%